The role of institutional quality on the performance in the export of coconut products - Jessie Lin; Insa Flachsbarth; Stephan von Cramon-Taubadel (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2018)
The literature that addresses the role of institutions in bilateral trade is extensive. However, research that link institutional quality to specific products and their different levels of value addition is lacking. In this study, we look into institutional quality, based on three indicators from the World Bank, and its indicator-specific effects on bilateral coconut trade. In particular, we study coconut products with varying degrees of value-addition. We utilize structural gravity models to measure how institutions affect the trade performance of the top 26 coconut producing countries to the top 15 importing economies over the years 1996-2016. Our results show that increased voice and accountability reduce bilateral trade of both highvalue and low-value coconut products while government effectiveness increases trade flows of high value products. Better control of corruption decreases trade of coconut oil. Furthermore, similarities in the voice and accountability and government effectiveness indicators between trading partners decrease trade of coconut products on an aggregate level. We conclude that each indicator has different effects on each of the product categories. We end by giving recommendations for policymakers that will help to improve the coconut export performance in their respective countries.
Keywords: F14; O43; Q17; Q18; 330; coconut supply chain; bilateral trade; gravity model; institutions; value-addition